2004
DOI: 10.1128/mcb.24.15.6742-6750.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of a Natural RNA Silencing Process in the Drosophila melanogaster Germ Line

Abstract: To date, few natural cases of RNA-silencing-mediated regulation have been described. Here, we analyzed repression of testis-expressed Stellate genes by the homologous Suppressors of Stellate [Su(Ste)] repeats that produce sense and antisense short RNAs. The Stellate promoter is dispensable for suppression, but local disturbance of complementarity between the Stellate transcript and the Su(Ste) repeats impairs silencing. Using in situ RNA hybridization, we found temporal control of the expression and spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
172
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 54 publications
9
172
0
1
Order By: Relevance
“…For instance, a Piwi-like protein, Twi1, is required for the conjugation-induced accumulation of small RNAs involved in programmed DNA elimination in T. thermophila (Lee and Collins 2006;Liu et al 2004b). The D. melanogaster Piwi-like genes Aubergine and Piwi have been implicated in both transcriptional, partly associated with histone H3 lysine 9 (H3K9) methylation, and post-transcriptional gene silencing (Aravin et al 2004;Kavi et al 2005;PalBhadra et al 2004). Members of the Argonaute-like class of proteins have been identified as key components of the RISC Rivas et al 2005;Zamore and Haley 2005).…”
Section: Nature Of the Ancestral Rnai Machinerymentioning
confidence: 99%
“…For instance, a Piwi-like protein, Twi1, is required for the conjugation-induced accumulation of small RNAs involved in programmed DNA elimination in T. thermophila (Lee and Collins 2006;Liu et al 2004b). The D. melanogaster Piwi-like genes Aubergine and Piwi have been implicated in both transcriptional, partly associated with histone H3 lysine 9 (H3K9) methylation, and post-transcriptional gene silencing (Aravin et al 2004;Kavi et al 2005;PalBhadra et al 2004). Members of the Argonaute-like class of proteins have been identified as key components of the RISC Rivas et al 2005;Zamore and Haley 2005).…”
Section: Nature Of the Ancestral Rnai Machinerymentioning
confidence: 99%
“…These fragments then target the specific destruction of homologous mRNAs. Such sense-antisense RNA-induced gene silencing has been well documented in the case of the silencing of Drosophila stellate repeats (Aravin et al 2001(Aravin et al , 2004. Modulation of the hyperexpression of Drosophila stellate repeats in testis is essential for male fertility, and studies have shown that the Su(Ste) repeats produce both sense and antisense RNAs that form dsRNA in vivo (Aravin et al 2001).…”
Section: Dsrna-dependent Mechanisms and Rnaimentioning
confidence: 99%
“…The helicases Armitage and Spindle-E are involved in biogenesis and loading of piRNAs into PIWI proteins as well as transposon silencing. 23,24 Maelstrom is fundamental for transcriptional transposon silencing and conserved in Hydra, Drosophila and mouse. 4,25,26 For comparison, we also included genes that encode microRNA machinery proteins (AGO1, AGO2, Dcr1, Dcr2 and GW182) in our analysis.…”
Section: Pirnas Are An Extremely Abundant Class Of Small Rnas In Nemamentioning
confidence: 99%